2003
DOI: 10.1186/cc1880
|View full text |Cite
|
Sign up to set email alerts
|

Poisoned patients as potential organ donors: postal survey of transplant centres and intensive care units

Abstract: BackgroundThe number of patients awaiting allograft transplantation in the UK exceeds the number of organs offered for transplantation each year. Most organ donors tend to be young, fit and healthy individuals who die because of trauma or sudden cardiac arrest. Patients who die from drug and poison intoxication tend to have similar characteristics but are less frequently offered as potential organ donors.MethodsA postal questionnaire survey of all transplantation centres and an equal number of intensive care u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(5 citation statements)
references
References 32 publications
(70 reference statements)
0
5
0
Order By: Relevance
“…The first published case report of a successful organ transplant from a donor, whose cause of death was cyanide toxicity, was published in 1987 [ 13 ]. Several additional case reports and small series echoed the findings that cyanide toxicity itself was not a contraindication to transplant [ 14 – 17 ]. Since 2006, hydroxocobalamin has established itself as the gold standard antidote for cyanide toxicity replacing amyl nitrate and sodium thiosulfate.…”
Section: Discussionmentioning
confidence: 97%
“…The first published case report of a successful organ transplant from a donor, whose cause of death was cyanide toxicity, was published in 1987 [ 13 ]. Several additional case reports and small series echoed the findings that cyanide toxicity itself was not a contraindication to transplant [ 14 – 17 ]. Since 2006, hydroxocobalamin has established itself as the gold standard antidote for cyanide toxicity replacing amyl nitrate and sodium thiosulfate.…”
Section: Discussionmentioning
confidence: 97%
“…Most of them indicated favorable long-term graft function and recipient survival ( Table 1 ) (7) , (8) , (9) , (10) , (11) , (12) , (13) , (14) , (15) . Although available data including the follow-up period are limited, it is most likely that the survival of organ grafts procured from donors who died due to methanol does not differ in the short- and long-term from transplants performed with organs from donors who died from other causes (16) .…”
Section: Discussionmentioning
confidence: 99%
“…The 2015 guidelines of the European Resuscitation Council concluded that there is an unproven benefit of transporting patients with ROSC to an HBO 2 therapy facility and that such a decision must be considered on a case-by-case basis [ 37 ]. Transfer to a tertiary referral hospital could be partly motivated by the possible consideration of organ donation [ 44 , 45 ].…”
Section: Discussionmentioning
confidence: 99%